Physicochemical, in vitro and in vivo evaluation of flurbiprofen microemulsion - NAEEM,MUHAMMAD (2015)
ABSTRACTFlurbiprofen, a potent nonsteroidal anti-inflammatory drug, is widely used for relief of pain in patients suffering from rheumatic diseases, migraine, sore throat and primary dysmenorrheal. However, this drug has many gastrointestinal side effects produced by its oral administration, such as gastric bleeding and peptic ulcer. These effects were responsible for non-compliance among patients, which ultimately results in treatment failure. The physicochemical properties of flurbiprofen, make it a suitable candidate for transdermal drug delivery, which can overcome the drawbacks of oral administration. In this sense, microemulsions have been proved to increase the cutaneous absorption of lipophilic drugs when compared to conventional drug delivery systems. The purpose of this study was to formulate and characterize gel based microemulsions, for topical delivery of flurbiprofen. Different gel bases, containing microemulsion and hydro-alcoholic solution of flurbiprofen, were developed and compared. In vitro study showed that gels containing microemulsion had a higher permeation rate than those containing hydro-alcoholic solutions. Additionally, formulation of Carbopol-I (microemulsion) showed higher percent of inhibition of inflammation than others bases. Further, skin irritation study demonstrated that Carbopol-I was none irritating. Flurbiprofen microemulsion incorporated on Carbopol-I showed physicochemical, in vitro and in vivo characteristics suitable for the development of alternative transdermal delivery formulation.